A study to assess the role of raised total leucocyte count in diagnosis of acute appendicitis - Kumar, Rajesh; Chauhan, Renu (International Journal of Advances in Medicine, 2020)
Introduction: Total Leucocyte Count (TLC) is an easily available and commonly performed investigation and studies have reported various degrees of leucocytosis in patients with acute appendicitis. This study was performed with the aim to assess the diagnostic validity of raised TLC count in acute appendicitis. Methods: This was a cross sectional study conducted from 2013 to 2015, in the Department of General Surgery, Indira Gandhi Medical College, Shimla. A clinical diagnosis of acute appendicitis was made based on detailed history taking, clinical examination, and laboratory investigations including TLC count. 50 patients with acute appendicitis were enrolled in the study by convenience sampling, after taking a written, informed consent. Appendicectomy specimen were sent for histopathological examination (HPE). Results: The mean age of the patients was 26.48 ± 12.28 years. 29 (58%) patients were male, and 21 (42%) were female. The negative appendicectomy rate in the present study was 14%. 7 (14%) were normal appendices, 31 (62%) inflamed appendices, 4 (8%) perforated appendices, and 8 (16%) gangrenous appendices as per HPE report. In our study, there were 12 (24%) cases of complicated appendicitis i.e., 8 (16%) cases of gangrenous appendicitis and 4 (8%) cases of perforated appendicitis). TLC had a sensitivity 76.74%, specificity 51.14%, positive predictive value 91.66%, and negative predictive value 28.57%. Conclusion: In our study, TLC was found to have low sensitivity and specificity for acute appendicitis. Hence, used alone, TLC may not be diagnostic of acute appendicitis. However, used in conjunction with other laboratory parameters, it will lead to improvement of diagnostic accuracy.